Influence Discipline Work, Safety and Health Work, And Promotion Position to Work Productivity - Hutahaean, Natal Angelia; Nadita, Sintia; Yunior, khomeny; Saputra, Hendra (International Journal Of Economics Social And Technology (IJEST), 2023)
PT Pelindo is an Indonesian State-Owned Enterprise that operates in the field of logistics, especially management relationship sea and development port. PT. Pelabuhan owns service business mainly from service ships, Service goods, and Pelabuhan general. And serve various types of loads like demolished load chest packs, bulk liquid or solid, unload load vehicles, and embarkation passengers. This company operates 94 ports located in 32 Provinces of Indonesia. PT. Indonesian Pelabuhan (Persero) Regional 1 Branch Belawan is one branch of Pelabuhan biggest in Indonesia. Study aim For explaining discipline work, safety, and health work, and promotion position to productivity working at PT. Pelabuhan Indonesian (Persero) Regional 1 Belawan Branch. Decline productivity Work PT. Pelabuhan Indonesia (Persero) Regional 1 Branch Belawan Which caused problems with discipline work, safety and health work, and promotion position, with spread questionnaire to 116 respondents or samples in study This. Method This uses validity tests, reliability tests, and multiple linear tests application SPSS27 data processing. The results of this research show that discipline Work is influential positive and significant to productivity Work employee PT. Pelabuhan Indonesia (Persero) Regional 1 Belawan Branch. Health and Safety Work influential positive and significant to productivity Work employee PT. Pelabuhan Indonesia (Persero) Regional 1 Belawan Branch. Promotion position influential positive and significant to productivity Work employee PT. Pelabuhan Indonesia (Persero) Regional 1 Branch Belawan. Adjusted R Square or R Test produces 0.851% or 85% Work Productivity can explained by Work Discipline, Occupational Safety and Health and Promotion Position, And the reis st influenced by other variables as much as 15%.